2007
DOI: 10.1111/j.1439-0469.2006.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic study of allozyme variation in natural populations of Drosophila antonietae (Insecta, Diptera)

Abstract: Drosophila antonietae is an endemic South American cactophilic species found in relictual xerophytic vegetation, mostly associated with Cereus hildmaniannus cactus. Low differentiation among populations of this species has been detected using several markers. In this work, we performed an allozyme genetic variability analysis of 11 natural populations of D. antonietae and included a discussion about the possible influences of several evolutionary processes that might be acting to maintain the pattern observed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
4
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 36 publications
5
22
4
6
Order By: Relevance
“…However, the geographic distances between populations of this species raises the question of the possibility of a real and current gene flow among them. Mateus & Sene (2007) antonietae and the cactus Cereus hildmaniannus, which is distributed mainly along the rivers basin, it has been proposed that there is gene flow among Drosophila populations through these rivers "corridors" following the cacti distribution, preventing genetic differentiation among them (Monteiro & Sene, 1995;Machado, 2003;Mateus & Sene, 2007). Our results did not support this hypothesis.…”
Section: Fig 1 Neighbor-joining Analysis For Three Drosophila Antoncontrasting
confidence: 80%
See 3 more Smart Citations
“…However, the geographic distances between populations of this species raises the question of the possibility of a real and current gene flow among them. Mateus & Sene (2007) antonietae and the cactus Cereus hildmaniannus, which is distributed mainly along the rivers basin, it has been proposed that there is gene flow among Drosophila populations through these rivers "corridors" following the cacti distribution, preventing genetic differentiation among them (Monteiro & Sene, 1995;Machado, 2003;Mateus & Sene, 2007). Our results did not support this hypothesis.…”
Section: Fig 1 Neighbor-joining Analysis For Three Drosophila Antoncontrasting
confidence: 80%
“…However, it was higher than the Fst detected by Mateus & Sene (2003) for D. antonietae in the within population spatial and temporal allozyme variation approaches (Fst = 0.0355 and 0.0023, respectivelly). Considering a among population approach, the Fst obtained here was lower (almost half the value) than those obtained using allozymes (Fst = 0.0723; Mateus & Sene, 2007) and microsatellite (Fst = 0.0730;Machado, 2003). In the same way, Reynolds et al (1983) genetic distances (Tabela 3) showed values consistents with the Fst, sugesting that despite the low genetic differentiation there is population structure among the populations studied.…”
Section: Populationscontrasting
confidence: 69%
See 2 more Smart Citations
“…However, adults are generalists because they visit other food sources in their environment (Morais et al, 1994). This ecological specificity of cactophilic Drosophila directly influences species distribution, as they are always associated with the host cactus distribution (Tidon-Sklorz & Sene, 1995;Manfrin & Sene, 2006;Mateus and Sene, 2007). Drosophila has been used as a research model for more than a century, and the first report of gene duplication was described by Bridges for the Bar locus in D. melanogaster over 70 years ago (Bridges, 1936).…”
Section: Introductionmentioning
confidence: 99%